The Apostle Paul in the Popular Jewish Imagination: The Case Study of the British Jewish Chronicle - Langton, Daniel R. (Studies in Christian-Jewish Relations, 2011)
A close reading of British weekly newspaper The Jewish Chronicle over the last 160 years suggests that popular Jewish attitudes towards the Apostle Paul, which are by no means pronounced, are best explained by his association with a series of controversies that resonate within the wider Jewish community. Somewhat unsurprisingly, Paul has been associated frequently with apostates and converts, with those who would abrogate the Torah, with those who would confuse the distinction between Jew and Christian, with missionary activities, and, arguably, with the phenomenon of Jewish self-hatred.